Rapid ultralow-friction rubber surface layer and construction method thereof

By preparing carbon films on the rubber surface and spraying two-dimensional intercalation materials, the problem of wear failure of rubber dynamic seals is solved, and the rapid and ultra-low friction characteristics are achieved. It is suitable for a variety of complex working conditions and is easy to industrially apply.

CN119241895AActive Publication Date: 2025-01-03LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411427424.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Rubber dynamic seals are prone to wear and fail under the action of high-pressure medium, resulting in seal leakage. The existing carbon film has a high friction coefficient during the run-in period, resulting in reduced lubrication efficiency and waste of resources.

Method used

Use vapor deposition technology to prepare carbon films on the rubber surface, and intercalation of MXene-based two-dimensional materials with other two-dimensional materials to form two-dimensional intercalation materials, sprayed to the surface of the carbon film to shorten the friction and run-in time and achieve ultra-low friction characteristic.

Benefits of technology

It significantly shortens the friction and running time, reduces the friction coefficient, improves the ultra-low friction performance of the rubber surface, is suitable for a variety of complex application conditions, and is easy to be used in large-area industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241895A_ABST
    Figure CN119241895A_ABST
Patent Text Reader

Abstract

According to the rapid ultralow-friction rubber surface layer and the construction method thereof, a carbon film is prepared on the surface of rubber by utilizing a vapor deposition technology, meanwhile, an MXene-based two-dimensional material and other two-dimensional materials are subjected to intercalation treatment to prepare a two-dimensional intercalation material, and finally, the two-dimensional intercalation material is sprayed to the surface of the carbon film to obtain the rapid ultralow-friction rubber surface layer. The two-dimensional intercalation material can rapidly form a heterojunction matching pair under the friction normal load effect, so that the friction running-in time is effectively shortened, and the ultralow friction characteristic is rapidly achieved. The process is not influenced by other external factors such as friction load and environment, and can be suitable for various complex application working conditions. According to the method, the technological process is easy to control, operability is high, the obtained rubber surface can achieve ultralow friction within an extremely short time, and large-area industrial application is easy to achieve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a fast ultra-low friction rubber surface layer and a construction method thereof, and in particular to a preparation method of a rubber surface carbon film + two-dimensional intercalation material, which is used for the preparation of dynamic seals and belongs to the field of solid lubricating materials and tribology. Background Art

[0002] There are a large number of sealing devices in modern industrial equipment to prevent leakage of working media and intrusion of external dust and foreign objects. Once the sealing medium leaks, it may cause material loss and equipment damage at the least, or even cause fire and explosion. Most dynamic seal leakage accidents are related to the sealing failure of the seal. Rubber has excellent properties such as good elastic recovery and pressure resistance, and is the most commonly used sealing material. However, after the rubber dynamic seal is installed in the sealing groove, it is squeezed and deformed by the high-pressure medium, and the friction coefficient with the steel groove wall and the sealing rod under the action of periodic stress is extremely high (µ>1). The friction heat generated by high friction can easily cause the rubber seal to soften and quickly wear out and fail, causing the high-pressure sealing medium to leak from the damaged part, thereby affecting the safe and reliable service of the equipment. Therefore, solving the problem of wear and failure of rubber seals must start with reducing friction.

[0003] Carbon film has excellent properties such as low adhesion to steel, low deposition temperature (deposition temperature ≤ 100°C, which will not cause fatal damage to the nitrile rubber matrix), controllable composition and mechanical strength, variable structure (such as multi-micro-nano structure, multi-element doping, etc.), and low friction and wear. Therefore, it is an ideal coating for achieving low friction on rubber surfaces. However, carbon films will experience a period of running-in at the beginning of friction (before reaching stable low friction), during which the friction coefficient is high (≥0.1, or even higher), which aggravates abnormal wear and failure of the film. If the running-in period is long, it will lead to reduced lubrication efficiency, waste of resources and time, and even cause the entire sealing system to fail. Therefore, how to construct a fast ultra-low friction rubber surface is the top priority for solving the wear and failure of rubber seals in the future. Summary of the invention

[0004] The purpose of the present invention is to provide a fast ultra-low friction rubber surface layer and a construction method thereof, which is to prepare a carbon film on the rubber surface by using vapor deposition technology, and at the same time, MXene-based two-dimensional materials and other two-dimensional materials are intercalated to prepare two-dimensional intercalation materials, and finally the two-dimensional intercalation materials are sprayed onto the surface of the carbon film. During the friction process, the two-dimensional intercalation material will quickly form a heterojunction pair at the friction interface under the action of the friction normal load, thereby effectively shortening the friction running-in time, and then quickly achieving ultra-low friction characteristics. In addition, this process is not affected by other external factors such as friction load and environment, and can be applied to a variety of complex application conditions.

[0005] 1. Fast ultra-low friction rubber surface layer and its construction method The fast ultra-low friction rubber surface layer of the present invention is firstly prepared by using vapor deposition technology to prepare a carbon film on the rubber surface, then intercalating MXene-based two-dimensional materials with other two-dimensional materials to prepare a two-dimensional intercalation material, and finally spraying the intercalation material onto the surface of the carbon film.

[0006] The method for preparing the above-mentioned fast ultra-low friction rubber surface layer comprises the following steps: 1) Rubber base cleaning: Cut the rubber sheet into 20×20mm 2 The rubber sheet is soaked in a 50~60℃ soapy water solution for ultrasonic cleaning for 30~45min to remove grease and dirt on the rubber surface; then it is taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 20~30min to remove possible residual soapy water solution; finally, it is blown dry with dry nitrogen and placed in a drying oven at 100~120℃ for another 20~30min to evaporate the residual moisture on the rubber surface; the above process is repeated 4~5 times; The rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, silicone rubber and EPDM rubber, the rubber surface roughness is ≤200nm, and the rubber thickness is 2-4mm.

[0007] 2) Preparation of amorphous carbon film: turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the Ar / CH4 flow ratio to 1.5:1, the substrate bias to -700 V, the gas pressure to 0.5-0.8 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 120-150 min; The amorphous carbon film is a hydrogen-containing or non-hydrogen-containing amorphous carbon film, and the film thickness is 500nm~1.0μm.

[0008] 3) Intercalation treatment of MXene-based two-dimensional materials and other two-dimensional materials: ① After drying, evenly distribute the MXene powder on the sample stage of the gas phase intercalation reaction chamber and evacuate to 10 -2 Up to 10 -3 Torr, then introduce hydrogen; ② heat the MXene sample in the reaction chamber to 300-400℃, keep it warm for 1-3h, and ensure that the hydrogen molecules are fully diffused into the interlayers of the MXene two-dimensional sheets; ③ turn off the hydrogen, let the reaction chamber cool naturally to room temperature and take it out; ④ disperse it with other two-dimensional materials in an organic solvent, and ultrasonically disperse it evenly to obtain a two-dimensional intercalation material; The MXene-based two-dimensional material is one or more of Ti-based, V-based, and Mo-based MXenes; other two-dimensional materials are one or more of graphene-based, molybdenum disulfide, and boron nitride; the mass ratio of MXene-based two-dimensional materials to other two-dimensional materials is 1~1.5:1, and the organic solvent is one of anhydrous ethanol and acetone.

[0009] 4) Spraying the two-dimensional intercalation material: The two-dimensional intercalation material solution is loaded into a portable sprayer, and the carbon film is preheated at the same time. Finally, the two-dimensional intercalation material is evenly sprayed onto the surface of the amorphous carbon film. After the solvent is completely evaporated, the fast ultra-low friction rubber surface of the present invention can be obtained.

[0010] The carbon film preheating temperature is 80-100° C., the spray gun working pressure is 2-4 MPa, the spray gun uniform moving speed is 2-4 cm / s, and the nozzle is 20-30 cm away from the substrate.

[0011] Figure 1 This is a schematic diagram of the cross-sectional structure of the fast ultra-low friction rubber surface constructed by the present invention. It can be seen that during the friction process, the friction contact interface of the two-dimensional intercalated material will quickly form a heterojunction pair under the action of the friction normal load, thereby effectively shortening the friction running-in time and quickly achieving ultra-low friction characteristics. The present invention effectively overcomes the technical difficulty of the long friction running-in period of the hard carbon-based coating on the soft surface of rubber, and the process is easy to control and has strong operability. The obtained rubber surface can quickly achieve ultra-low friction and is easy to realize large-scale industrial application.

[0012] 2. Rubber Surface Performance Test Constructed by the Present Invention 1. Break-in time The friction and running-in time of the rubber surface constructed by the present invention was tested using a ball-disc rotary friction and wear tester, and the results showed that the running-in time was 30 to 60 seconds.

[0013] 2. Friction coefficient Figure 2 The friction coefficient curve of the fast ultra-low friction rubber surface constructed by the present invention. The tribological performance of the rubber surface constructed by the present invention was evaluated using a friction and wear tester. The friction conditions were: ball-disc rotation mode, normal load 10N, friction pair φ6mm GCr15 steel ball, and test environment was air. The results showed that the friction coefficient of conventional pure carbon film was high (>0.18), while the friction coefficient of the rubber surface constructed by the present invention was significantly reduced (0.04~0.08).

[0014] In summary, the present invention has the following advantages compared with the prior art: 1. Two-dimensional intercalation material is sprayed on the surface of the carbon film. During the friction process, the friction contact interface of the two-dimensional intercalation material will quickly form a heterojunction pair under the action of the normal load, thereby effectively shortening the friction running-in time and quickly achieving ultra-low friction characteristics.

[0015] 2. The present invention effectively overcomes the current technical difficulty of the long friction running-in period of hard carbon-based coatings on soft rubber surfaces, and the process is not affected by other external factors such as friction load and environment, and can be applied to a variety of complex working conditions.

[0016] 3. The process of the present invention is simple and easy to control, with strong operability. The constructed rubber surface can quickly achieve ultra-low friction characteristics and is easy to realize large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a schematic diagram of the cross-sectional structure of the fast ultra-low friction rubber surface constructed by the present invention.

[0018] Figure 2 The friction coefficient curves of the rubber surface constructed by the present invention, the original rubber and the single-layer carbon film on its surface are shown. DETAILED DESCRIPTION

[0019] The construction method and performance of the fast ultra-low friction rubber surface of the present invention are further described below through specific examples.

[0020] Example 1 (1) Cut a 300×300×2 mm black nitrile rubber sheet (surface finish Ra<200 nm, thickness 3 mm) into 20×20 mm 2 The rubber sheet was ultrasonically cleaned in a 60℃ soap solution for 30 minutes to remove grease and dirt on the rubber surface; then it was taken out and ultrasonically cleaned in 90℃ distilled water for 30 minutes to remove possible residual soap solution; finally, it was blown dry with dry nitrogen and placed in a drying oven at 120℃ for another 20 minutes to evaporate the residual moisture on the rubber surface. The above process was repeated 5 times; (2) Place the cleaned rubber substrate in the magnetron sputtering vacuum chamber, close the vacuum chamber door, and evacuate the vacuum chamber to ≤2.0×10 –3 Pa; turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8 cm, the target current to 3 A, the argon flow rate to 45 sccm, the CH4 flow rate to 30 sccm, the substrate bias to -700 V, the gas pressure to 0.5 Pa, the duty cycle to 40%, the frequency to 60 KHz, and the deposition time to 120 min. After the deposition is completed, wait for the temperature in the vacuum chamber to cool to room temperature before taking out the sample.

[0021] (3) First, the Ti3C2MXene powder was dried in a vacuum oven at 80 °C for 12 h. Then, the dried MXene powder sample was placed on the sample stage of the gas phase intercalation reaction chamber and the reaction chamber was evacuated to 10 -2 Up to 10 -3Torr. Hydrogen with a purity of 99.999% was introduced into the reaction chamber, and the pressure of the reaction chamber was adjusted to 1 atm (atmospheric pressure) to ensure that the hydrogen fully filled the entire reaction chamber. The MXene sample in the reaction chamber was heated to 300°C and maintained for 1 hour to ensure that the hydrogen molecules had enough time to diffuse into the MXene interlayers and form a stable Ti3C2MXene material with an enlarged interlayer spacing. After the above process was completed, the hydrogen was turned off and the reaction chamber was allowed to cool naturally to room temperature in a hydrogen atmosphere.

[0022] (4) Take 25 mg of Ti3C2MXene and 25 mg of MoS2 powder prepared by the above method respectively, and dissolve them in 50 mL of anhydrous ethanol. Use an ultrasonic device to perform ultrasonic treatment at a power of 300 W for 60 minutes to ensure sufficient dispersion to obtain Ti3C2MXene / MoS2 two-dimensional intercalation material.

[0023] (5) The Ti3C2MXene / MoS2 two-dimensional intercalation material solution prepared above is loaded into a portable sprayer, and the carbon film prepared in step (2) is preheated to 80°C; a nitrogen bottle is connected to the spray gun, and the flow rate is set to 15 L / min to ensure that the internal environment of the spray gun is a nitrogen atmosphere during operation; the working pressure of the air spray gun is set to 2MPa, the nozzle is 20cm away from the substrate, and the spraying is completed at a uniform speed of 2cm / s; after the spraying is completed, the substrate is continued to be heated at 100°C for 30 minutes to ensure that the anhydrous ethanol is completely evaporated, and the rubber surface constructed by the present invention is obtained by naturally cooling to room temperature. The friction coefficient of the nitrile rubber surface reaching a stable state under a load of 10N is 0.05, and the running-in period takes only 45 seconds.

[0024] Example 2 (1) The silicone rubber pre-cleaning step is the same as in Example 1. Wherein: the silicone rubber surface finish Ra is less than 200 nm, and the thickness is 3 mm.

[0025] (2) Place the cleaned rubber substrate in the magnetron sputtering vacuum chamber, close the vacuum chamber door, and evacuate the vacuum chamber to ≤2.0×10 –3 Pa; turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8 cm, the target current to 3 A, the argon flow rate to 45 sccm, the substrate bias to -700 V, the gas pressure to 0.5 Pa, the duty cycle to 40%, the frequency to 60 KHz, and the deposition time to 120 min. After the deposition is completed, wait for the temperature in the vacuum chamber to cool to room temperature before taking out the sample.

[0026] (3) First, the V4C3MXene powder was dried in a vacuum oven at 80 °C for 12 h. Then, the dried MXene powder was placed on the sample stage of the gas phase intercalation reaction chamber and the reaction chamber was evacuated to 10 -2 Up to 10 -3Torr. Hydrogen with a purity of 99.999% was introduced into the reaction chamber, and the pressure of the reaction chamber was adjusted to 1 atm (atmospheric pressure) to ensure that the hydrogen fully filled the entire reaction chamber. The MXene sample in the reaction chamber was heated to 400°C and maintained for 2 hours to ensure that the hydrogen molecules had enough time to diffuse into the MXene interlayers and form a stable V4C3MXene material with an enlarged interlayer spacing. After the above process was completed, the reaction chamber was naturally cooled to room temperature in a hydrogen atmosphere.

[0027] (4) Take 25 mg of the V4C3MXene and 25 mg of graphene powder prepared above respectively, and dissolve them in 50 mL of acetone solution. Use an ultrasonic device to perform ultrasonic treatment at a power of 300 W for 60 minutes to ensure sufficient dispersion to obtain the V4C3MXene / graphene two-dimensional intercalation material.

[0028] (5) The V4C3MXene / graphene two-dimensional intercalation material solution prepared above is loaded into a portable sprayer, and the carbon film prepared in step (2) is preheated to 100°C; a nitrogen bottle is connected to the spray gun, and the flow rate is set to 15L / min to ensure that the internal environment of the spray gun is a nitrogen atmosphere during operation; the working pressure of the air spray gun is set to 4MPa, the nozzle is 30cm away from the substrate, and the spraying is completed at a uniform speed of 4cm / s; after the spraying is completed, the substrate is continued to be heated at 100°C for 30 minutes to ensure that the acetone solution is completely evaporated, and the rubber surface constructed by the present invention is obtained by naturally cooling to room temperature. The friction coefficient of the silicone rubber surface reaching a stable state under a load of 10N is 0.08, and the running-in period takes only 30 seconds.

[0029] Example 3 (1) The hydrogenated nitrile rubber pre-cleaning step is the same as in Example 1. Wherein: the silicone rubber surface finish Ra is less than 200 nm, and the thickness is 2 mm.

[0030] (2) The preparation of the hydrogen-free carbon film on the surface of hydrogenated nitrile rubber is the same as in Example 2; (3) First, the Mo2C MXene powder was dried in a vacuum oven at 80 °C for 12 h. Then, the dried MXene powder sample was placed on the sample stage of the gas phase intercalation reaction chamber and the reaction chamber was evacuated to 10 -2 ~10 -3 Torr. Hydrogen with a purity of 99.999% was introduced into the reaction chamber, and the pressure of the reaction chamber was adjusted to 1 atm (atmospheric pressure) to ensure that the hydrogen fully filled the entire reaction chamber. The MXene sample in the reaction chamber was heated to 350°C and maintained for 1.5 hours to ensure that the hydrogen molecules had enough time to diffuse into the MXene interlayers and form a stable Mo2C MXene material with an enlarged interlayer spacing. After the above process was completed, the reaction chamber was naturally cooled to room temperature in a hydrogen atmosphere.

[0031] (4) Take 30 mg of the Mo2C MXene and 20 mg of boron nitride powder prepared above, respectively, and dissolve them in 50 mL of acetone solution. Use an ultrasonic device to perform ultrasonic treatment at a power of 300 W for 60 minutes to ensure that they are fully dispersed to obtain the Mo2C MXene / graphene two-dimensional intercalation material.

[0032] (5) The Mo2C MXene / BN two-dimensional intercalation material solution prepared above is loaded into a portable sprayer, and the carbon film prepared in step (2) is preheated to 90°C; a nitrogen bottle is connected to the spray gun, and the flow rate is set to 15 L / min to ensure that the internal environment of the spray gun is a nitrogen atmosphere during operation; the working pressure of the air spray gun is set to 3MPa, the nozzle is 25cm away from the substrate, and the spraying is completed at a uniform speed of 3cm / s; after the spraying is completed, the substrate is continued to be heated at 100°C for 30 minutes to ensure that the acetone is completely evaporated and naturally cooled to room temperature to obtain the rubber surface constructed by the present invention. The friction coefficient of the hydrogenated nitrile rubber surface reaching a stable state under a load of 10N is 0.06, and the running-in period takes only 60 seconds.

Claims

1. A fast ultra-low friction rubber surface layer, which is first prepared by using vapor deposition technology to prepare a carbon film on the rubber surface, then intercalating MXene-based two-dimensional materials with other two-dimensional materials to prepare a two-dimensional intercalation material, and finally spraying it onto the surface of the carbon film.

2. A method for constructing a fast ultra-low friction rubber surface layer as claimed in claim 1, characterized in that: The following steps are involved: 1) Rubber base cleaning: Cut the rubber sheet into 20×20mm 2 The rubber sheet is soaked in a 50~60℃ soapy water solution for ultrasonic cleaning for 30~45min to remove grease and dirt on the rubber surface; then it is taken out and soaked in 90~95℃ distilled water for ultrasonic cleaning for 20~30min to remove possible residual soapy water solution; finally, it is blown dry with dry nitrogen and placed in a drying oven at 100~120℃ for another 20~30min to evaporate the residual moisture on the rubber surface; the above process is repeated 4~5 times; 2) Preparation of amorphous carbon film: turn on the graphite target sputtering power supply, adjust the target-substrate distance to 8-12 cm, the target current to 3 A, the argon flow rate to 45-60 sccm, the Ar / CH4 flow ratio to 1.5:1, the substrate bias to -700 V, the gas pressure to 0.5-0.8 Pa, the duty cycle to 40-45%, the frequency to 60-70 KHz, and the deposition time to 120-150 min; 3) Intercalation treatment of MXene-based two-dimensional materials and other two-dimensional materials: ① After drying, evenly distribute the MXene powder on the sample stage of the gas phase intercalation reaction chamber and evacuate to 10 -2 Up to 10 -3 Torr, then introduce hydrogen; ② heat the MXene sample in the reaction chamber to 300-400℃, keep it warm for 1-3h, and ensure that the hydrogen molecules are fully diffused into the interlayers of the MXene two-dimensional sheets; ③ turn off the hydrogen, let the reaction chamber cool naturally to room temperature and take it out; ④ disperse it with other two-dimensional materials in an organic solvent, and ultrasonically disperse it evenly to obtain a two-dimensional intercalation material; 4) Spraying the two-dimensional intercalation material: The two-dimensional intercalation material solution is loaded into a portable sprayer, and the carbon film is preheated at the same time. Finally, the two-dimensional intercalation material is evenly sprayed onto the surface of the amorphous carbon film. After the solvent is completely evaporated, the fast ultra-low friction rubber surface of the present invention can be obtained.

3. The method for constructing a fast ultra-low friction rubber surface layer as claimed in claim 2, characterized in that: In step 1), the rubber substrate is one of nitrile rubber, hydrogenated nitrile rubber, silicone rubber and EPDM rubber, the rubber surface roughness is ≤200nm, and the rubber thickness is 2-4mm.

4. The method for constructing a fast ultra-low friction rubber surface layer as claimed in claim 2, characterized in that: In step 2), the amorphous carbon film is a hydrogen-containing or non-hydrogen-containing amorphous carbon film, and the film thickness is 500nm~1.0µm.

5. The method for constructing a fast ultra-low friction rubber surface layer as claimed in claim 2, characterized in that: In step 3), the MXene-based two-dimensional material is one or more of Ti-based, V-based, and Mo-based MXenes; other two-dimensional materials are one or more of graphene-based, molybdenum disulfide, and boron nitride; the mass ratio of MXene-based two-dimensional materials to other two-dimensional materials is 1~1.5:1, and the organic solvent is one of anhydrous ethanol and acetone.

6. A method for constructing a fast ultra-low friction rubber surface layer as claimed in claim 2, characterized in that: The carbon film preheating temperature is 80-100° C., the spray gun working pressure is 2-4 MPa, the spray gun uniform moving speed is 2-4 cm / s, and the nozzle is 20-30 cm away from the substrate.

Citation Information

Patent Citations

  • Dual-regulation two-dimensional MXene composite membrane and preparation method thereof

    CN115041027A

  • Rubber surface low-humidity-sensitivity ultralow-friction carbon-based composite coating and preparation method thereof

    CN116651714A

  • Rubber surface ultralow-friction carbon-based multi-layer composite coating and construction method thereof

    CN116657138A

  • Titanium alloy with segmented heterojunction composite film on surface and preparation method of titanium alloy

    CN116856034A

  • MXene / MoS2 composite material, preparation method thereof, lubricating paint, lubricating coating and application

    CN118359228A